Memory : Neurochemical and Abnormal Perspectives - weinman John Hunter, Jackie (Harwood academic publishers, 1991)
Reviews of the work on the neurochemistry of memory, on dysfunction and individual differences provide a range of insights into the structure and function of memory mechanisms and enable the reader to understand the reciprocal relation of this work to current psychological approaches and models